Formulasi Dan Uji Stabilitas Fisik Sediaan Hair Tonic Ekstrak Daun Belimbing Wuluh (Averrhoa Blimbi L.) - Datulamban, Melindasari S; Arbie, Srimuliani; Supu, Rini Daud Supu (LPPM Universitas Bina Mandiri Gorontalo, 2024)
This study aims to determine the effect of Formula I, II, and III on the physical stability of Hair tonic preparations. The research method used is a true experimental laboratory that aims to see or determine the best proportion of active ingredients in making hair tonic preparations with variations in the concentration of star fruit leaf extract, namely F1 (5%), F2 (10%), and F3 (15%), using the Physical Stability test parameters of the preparation, which include Organoleptic tests, homogeneity, pH, and Viscosity. The results of physical stability studies show that in organoleptic tests, F1, F2, and F3 have the same shape, aroma, and taste. Moreover, there are color differences. In the F1 homogeneity test, F2 and F3 have homogeneity. In the pH test of hair tonic preparations, the extract of Wuluh star fruit leaf at F1 (5%) before the cycling test averaged 4.50, while after the cycling test it averaged 4.57. F2 (10%) before the cycling test averaged 4.56; after the cycling test averaged 4.82; before the cycling test averaged 5.97; after the cycling test averaged 6.13. The viscosity value before the cycling test averaged 16183, while after the cycling test it averaged 15133. F2 (10%) before the cycling test averaged 16533, while after the cycling test it averaged 15433. F3 (15%) before the cycling test averaged 16866, while after the cycling test it averaged 15666.